French Ecocriticism From the Early Modern Period to the Twenty-First Century - Finch-Race, Daniel A.; Posthumus, Stephanie (Studien zu Literatur, Kultur und Umwelt / Studies in Literature, Culture, and the Environment, 2017)
This book expounds fruitful ways of analysing matters of ecology, environments, nature, and the non-human world in a broad spectrum of material in French. Scholars from Canada, France, Great Britain, Spain, and the United States examine the work of writers and thinkers including Michel de Montaigne, Victor Hugo, Émile Zola, Arthur Rimbaud, Marguerite Yourcenar, Gilbert Simondon, Michel Serres, Michel Houellebecq, and Éric Chevillard. The diverse approaches in the volume signal a common desire to bring together form and content, politics and aesthetics, theory and practice, under the aegis of the environmental humanities.